The Antipruritic Effect of Phototherapy - Legat, Franz J. (Frontiers in Medicine, 2018)
Phototherapy is widely used to treat inflammatory skin diseases such as psoriasis and atopic dermatitis. Repeated suberythemogenic doses of UV-light reduce inflammation in these diseases and ultimately may lead to a complete disappearance of cutaneous symptoms for weeks or months. Chronic pruritus is an important and highly distressing symptom of many of these inflammatory skin diseases. Interestingly, pruritus is also reduced or completely abolished by UV-treatment of psoriasis and atopic dermatitis, and sometimes reduction of pruritus is the first indication for skin improvement by phototherapy. The cutaneous nervous system is an integral part of skin anatomy, and free nerve endings of sensory cutaneous nerve fibers reach up into the epidermis getting in close contact with epidermal cells and mediators from epidermal cells released into the intercellular space. Stimulation of “pruriceptors” within this group of sensory nerve fibers generates a neuronal signal eventually transmitted via the dorsal root and the spinal cord to the brain, where it is recognized as “itch”. UV-light may directly affect these sensory nerve fibers or, via the release of mediators from surrounding skin cells, indirectly modulate their function as well as the transmission of itch to the central nervous system inducing the clinically recognized antipruritic effect of phototherapy.